Single crystal polarized neutron diffraction study of the magnetic structure of HoFeO3. (17th August 2017) - Chatterji, T; Stunault, A; Brown, P J
Abstract: Polarised neutron diffraction measurements have been made on HoFeO3 single crystals magnetised in both the [0 0 1] and [1 0 0] directions ( Pbnm setting). The polarisation dependencies of Bragg reflection intensities were measured both with a high field of H = 9 T parallel to [0 0 1] at T = 70 K and with the lower field H = 0.5 T parallel to [1 0 0] at T = 5, 15, 25 K. A Fourier projection of magnetization induced parallel to [0 0 1], made using the hk 0 reflections measured in 9 T, indicates that almost all of it is due to alignment of Ho moments. Further analysis of the asymmetries of general reflections in these data showed that although, at 70 K, 9 T applied parallel to [0 0 1] hardly perturbs the antiferromagnetic order of the Fe sublattices, it induces significant antiferromagnetic order of the Ho sublattices in the x − y plane, with the antiferromagnetic components of moment having the same order of magnitude as the induced ferromagnetic ones. Strong intensity asymmetries measured in the low temperature Γ 2 structure with a lower field, 0.5 T ∥ [1 0 0] allowed the variation of the ordered components of the Ho and Fe moments to be followed. Their absolute orientations, in the 180 ∘ domain stabilised by the field were determined relative to the distorted perovskite structure. This relationship fixes the sign of the Dzyalshinski–Moriya (D-M) interaction which leads to the weak ferromagnetism. Our results indicate that the combination of strong y -axis anisotropy of the Ho moments and Ho-Fe exchange interactions breaks the centrosymmetry of the structure and could lead to ferroelectric polarization.